2018
DOI: 10.1097/ccm.0000000000002889
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ventilator-Associated and Early Postoperative Pneumonia Through Tapered Endotracheal Tube Cuffs: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Application of tapered endotracheal tube cuffs did not reduce hospital-acquired pneumonia incidence among ICU and postoperative patients. Further research should examine the impact of concomitant use of tapered cuffs with continuous cuff pressure monitoring and subglottic secretion drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
1
24
0
2
Order By: Relevance
“…The use of specific, targeted polymerase chain reaction (PCR) may allow shortening this time to 24-36 h., but for specific pathogens and specific resistance mechanisms. A potential future workup process will be to use multiplex PCR (blue box) to identify within less than 6 h pathogens responsible for VAP and their resistance to antimicrobials chloride at preventing VAP or improving objective outcomes [101][102][103][104]. Likewise, manually monitoring cuff pressures every 8 h to minimize inadvertent drops in endotracheal tube cuff pressure was no better at preventing VAP, decreasing length-of-stay, or lowering mortality in a recent single center study compared to checking cuff pressures only at intubation, following frank tube migration, or detection of a cuff pressure leak [105].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of specific, targeted polymerase chain reaction (PCR) may allow shortening this time to 24-36 h., but for specific pathogens and specific resistance mechanisms. A potential future workup process will be to use multiplex PCR (blue box) to identify within less than 6 h pathogens responsible for VAP and their resistance to antimicrobials chloride at preventing VAP or improving objective outcomes [101][102][103][104]. Likewise, manually monitoring cuff pressures every 8 h to minimize inadvertent drops in endotracheal tube cuff pressure was no better at preventing VAP, decreasing length-of-stay, or lowering mortality in a recent single center study compared to checking cuff pressures only at intubation, following frank tube migration, or detection of a cuff pressure leak [105].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
“…Head-of-bed elevation [116] May lower rates Understudied, few and contradictory randomized trials Tapered endotracheal tube cuffs and ultrathin polyurethane [102,104] No impact In vivo studies document persistently high rates of subclinical aspiration despite the theoretical advantages of these designs Automated endotracheal tube cuff pressure monitoring [106] May lower rates Understudied, merits further evaluation [92,123,125] May increase VAP rates Observational studies and some meta-analyses suggest higher VAP rates but a recent large randomized trial found no impact VAP prevention bundles [128] Likely lower VAP rates Extensively studied, almost exclusively in before-after and time-series analyses. May be associated with lower mortality rates.…”
Section: Intervention Probable Impact On Vap Rates Commentsmentioning
confidence: 99%
“…Preventive strategies mainly target optimization of basic infection control measures, avoidance of delayed extubation, biofilm formation on the endotracheal tube and of micro-aspiration of subglottic secretions, prevention of bacterial translocation from stomach to oropharynx, and modulation of oropharyngeal colonization [48]. Regarding the last of these, the value of chlorhexidine oral care has been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Maertens and colleagues further evaluated tapered versus conventional cuffs by combining these two trials with four others (total 1,324 patients). 60 On meta-analysis, they found no difference between cuff shapes in the frequency of hospital-acquired pneumonia nor any signals in the individual studies suggesting differences in duration of mechanical ventilation (three trials), ICU length of stay (four trials), or mortality (three trials). There is a paucity of additional studies on polyurethane cuffs that include data on clinical outcomes, but for the present at least there is no clear signal of clinical benefit.…”
Section: Endotracheal Tube Cuff Design and Pressure Monitoringmentioning
confidence: 95%